A complete chitinolytic system in the atherinopsid pike silverside Chirostoma estor: gene expression and activities. Issue 6 (10th May 2016) - Pohls, P.; González‐Dávalos, L.; Mora, O.; Shimada, A.; Varela‐Echavarria, A.; Toledo‐Cuevas, E. M.; Martínez‐Palacios, C. A.
Abstract : The expression and digestive activity of pike silverside Chirostoma estor endogenous chitinases were analysed in samples from four life stages: whole eggs; larvae; juvenile intestine and hepatopancreas and adult intestine and hepatopancreas. A chitinase cDNA was cloned and partially sequenced (GenBank accession number: FJ785521). It was highly homologous to non‐acidic chitinase sequences from other fish species, suggesting that it is a chitotriosidase. Quantitative PCR showed that this chitinase was expressed throughout the life span of C. estor, with maximum expression in the hepatopancreas of juveniles. Chitotriosidase and chitobiosidase activities were found at all life stages, along with a very high level of N ‐acetyl glucosaminidase (NAGase). The chitotriosidase activity could be encoded by the cloned complementary (c)DNA, although additional chitinase genes may be present. The chitotriosidase activity appeared to be transcriptionally regulated only at the juvenile stage. The expression and activity of chitinases tended to increase from the early to juvenile stages, suggesting that these variables are stimulated by chitin‐rich live food. Nevertheless, the feeding of juvenile and adult fish with both live food and a balanced commercial diet seemed to provoke significant reductions in pancreatic NAGase secretion and/or synthesis in the gut. Moreover, all chitinase activities were lower in adults, probably reflecting a higher intake and use of the balanced diet. The observation of chitotriosidase and chitobiosidase activities together with a very high NAGase activity suggest the presence of a complete and compensatory chitinolytic chitinase system that enables this stomachless short‐gut fish species to use chitin as an energy substrate. These novel findings suggest that dietary inclusions of chitin‐rich ingredients or by‐products might reduce the farming costs of C. estor without impairing performance.